High-intensity ultrasound of chicken myofibrillar protein under reduced-salt conditions: effect on emulsifying and interfacial properties - Linmeng Wang; Yanfang Zhou; Qing Yang; Lei Fu; Ke Li; Yanhong Bai (Food Science of Animal Products)
In this study, the effects of high-intensity ultrasound (HIU, frequency 20 kHz, amplitude 60%, power 450 W) for 0, 6, and 9 min on the emulsifying properties of chicken myofibrillar protein (MP) under different NaCl concentrations (0.2, 0.3, 0.4, and 0.5 mol/L) were investigated. The results showed that the increasing NaCl concentration and prolonged HIU treatment time significantly enhanced the emulsifying activity, the emulsifying stability and storage stability of MP emulsion were increased significantly (P < 0.05), and the particle size of MP emulsion were decreased significantly (P < 0.05). HIU pretreatment decreased the interfacial tension, and increased the apparent viscosity and the absolute zeta-potential of reduced-NaCl MP emulsions. Compared with the non-HIU group at 0.5 mol/L NaCl, the emulsions stability was significantly improved when the HIU time was extended to 9 min under 0.3 mol/L NaCl (P < 0.05). Sodium dodecyl sulfate-polyacrylamide gel electrophoresis result of interfacial MP showed that the band strength of myosin heavy chain and actin significantly increased after 9 min-HIU treatment at both 0.3 and 0.5 mol/L NaCl. Circular dichroism analysis showed that the random coil relative content of interfacial MP was decreased significantly (P < 0.05), and the relative content of α-helix and β-sheet were increased (P < 0.05) after HIU. Extended HIU time could partially alternative the effect of NaCl on the emulsification properties of MP, and improve the stability of the interfacial protein structure and MP emulsion in reduced-salt conditions, which facilitated the processing of lower salt emulsion-based meat products.